Influencing factors on consumers purchase decision of smartphones in Lagos State, Nigeria - Elochukwu, Ozala John; Abu Bakar, Elistina; Md Jusoh, Zuroni (Human resouce Management Academic Research Society, 2023)
Despite accounting for one-sixth of the global population, Africa's use of mobile technology applications is minimal compared to other rapidly expanding nations. Very few studies have examined the factors influencing smartphone purchase decisions, particularly those made by Lagos residents in Nigeria. The paper evaluates what influences consumers’ smartphone purchases in Lagos State, Nigeria. A structured questionnaire was designed and distributed to 375 respondents sampled through multistage random sampling. The result of the analysis denoted that system quality was the most significant factor influencing smartphone purchases, followed by brand and price. However, social influence tends to be insignificant. These three factors can explain 16.2 of the purchase decision. Lagos people make their own decision regarding purchasing and will not be influenced by social pressure, such as their peers. This study can serve as a framework to enhance the telecommunication industry in Nigeria. The findings of this research can also help industry players to market their products and subsequently boost the Nigerian economy